(untitled) - White, Martin (London, 2005)
There are many benefits in using content management software (CMS) to support content authoring and site management for both intranets and websites. These benefits can only be realized when the organization has developed a content management strategy and undertaken a rigorous analysis of the functionality that the CMS must provide, taking into account the Total Cost of Implementation of a CMS application. Information professionals will increasingly play an important role in developing content management strategies and managing intranets and websites, using their professional skills in carrying out information audits, identifying the information needs of users, and developing information architectures and metadata schemes. This essential book provides step-by-step guidance on how to develop a content management strategy, sets out the elements of a content management system and provides advice on the specification, selection, implementation and management of content management software. This practical handbook takes advantage of the author's extensive consulting experience in supporting CMS implementations in a wide range of organizations in the UK, Europe and the USA, including government agencies, charities and multinational businesses. It is of great value to information staff at all levels who are involved in the process of using a CMS to support the development of websites and intranets.
Keywords: Information resources management,Library services